2021
DOI: 10.3390/cancers13163935
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Permeability Barrier Dysfunction in a Murine Model of Cutaneous Field Cancerization Following Chronic UV-B Irradiation: Implications for the Pathogenesis of Skin Cancer

Abstract: Chronic ultraviolet B (UV-B) irradiation is known to be one of the most important hazards acting on the skin and poses a risk of developing photoaging, skin with cutaneous field cancerization (CFC), actinic keratosis (AKs), and squamous cell carcinomas (SCCs). Most of the UV-B light is absorbed in the epidermis, affecting the outermost cell layers, the stratum corneum, and the stratum granulosum, which protects against this radiation and tries to maintain the permeability barrier. In the present work, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…As most of the UVB light is absorbed in the epidermis 48 , the outermost cell layers, the stratum corneum, and the stratum granulosum were most affected, resulting in a breakdown of the epidermal physical barrier (protects against radiation and tries to maintain of permeability) 49 . Santiago et al found that skin received chronic UVB radiation had a higher skin surface pH value, with the permeability barrier and stratum corneum hydration severely compromised in a Murine Model of Cutaneous Field Cancerization 50 . This is consistent with our study that female skin exhibits high transcutaneous water dissipation, low hydration and neutral pH in Guangzhou with longer sunshine duration.…”
Section: Discussionmentioning
confidence: 99%
“…As most of the UVB light is absorbed in the epidermis 48 , the outermost cell layers, the stratum corneum, and the stratum granulosum were most affected, resulting in a breakdown of the epidermal physical barrier (protects against radiation and tries to maintain of permeability) 49 . Santiago et al found that skin received chronic UVB radiation had a higher skin surface pH value, with the permeability barrier and stratum corneum hydration severely compromised in a Murine Model of Cutaneous Field Cancerization 50 . This is consistent with our study that female skin exhibits high transcutaneous water dissipation, low hydration and neutral pH in Guangzhou with longer sunshine duration.…”
Section: Discussionmentioning
confidence: 99%
“…Santiago, J.L. et al [ 7 ] developed a preclinical model of skin with cutaneous field cancerization after chronic ultraviolet (UV) B light exposure in immunocompetent SKH1 aged mice. Compared to non-irradiated controls, UV-B irradiated skin demonstrated impairments in trans-epidermal water loss, stratum corneum hydration, and surface pH in a dose-dependent manner.…”
Section: Clinical Snippetsmentioning
confidence: 99%
“…UV-B radiation is potentially harmful to living organisms exposed to sunlight. Excessive UV-B radiation not only causes skin cancers in humans (D’Orazio et al 2013 ; Santiago et al 2021 ), but also leads to cell death in plants physiologically featured with wilting, yellowing or bleaching of leaves (Jenkins 2009 ). UV-B stress can induce damage directly at the DNA level by producing cyclobutene pyrimidine dimers (CPDs), and pyrimidine (6–4) pyrimidinone photoproducts (6–4 PPs) (Britt 1995 ; Molinier et al 2008 ; Quaite et al 1994 ; Sinha and Hader 2002 ; Takahashi et al 2011 ).…”
Section: Uv-b Stress-induced Damagementioning
confidence: 99%